A study of the electronic and physical properties of SnO2 thin films as a function of substrate temperature. Issue 15 (15th October 2019) - Erken, O.; Ozkendir, O.M.; Gunes, M.; Harputlu, E.; Ulutas, C.; Gumus, C.
Abstract: In this work, tin dioxide (SnO2 ) thin films were prepared at various substrate temperatures (380–440 °C, in steps of 20 °C) on glass substrates by the Spray Pyrolysis Method. X-ray Diffraction (XRD) measurements revealed that the SnO2 thin films were formed in a tetragonal crystallized structure. The electronic structure of the tin dioxide thin films that were prepared at several substrate temperatures were investigated with the collected X-ray Absorption Spectroscopy (XAS) data. The crystal structure analysis was also supported by the Extended X-ray Absorption Fine Structure (EXAFS) data analysis extracted from the X-ray Absorption Fine Structure (XAFS) data. Unstable crystal behaviors were detected in the samples due to metastable SnO structure formations as a result of phase transitions from the SnO to SnO2 structure during the annealing processes. Clear information on the atomic displacements in the samples as a picture of the crystal mechanism was obtained from the analysis of EXAFS data. The SnO2 thin films were found to exhibit high transmittance (average 90%) in the 400–1100 nm interval. The thickness of the SnO2 thin film ( t ) and refractive index ( n ) were calculated from transmittance spectra in the visible region using envelope method. The direct energy band gaps of the films obtained were 4.01–4.09 eV. Atomic force microscope (AFM) measurements were performed in order to investigate the surface roughness of the SnO2 thin films.